Effectiveness and safety of rivaroxaban in patients with venous thromboembolism and active cancer: A subanalysis of the J'xactly study. Issue 3 (March 2023) - Hisatake, Shinji; Ikeda, Takanori; Fukuda, Ikuo; Nakamura, Mashio; Yamada, Norikazu; Takayama, Morimasa; Maeda, Hideaki; Yamashita, Takeshi; Mo, Makoto; Yamazaki, Tsutomu; Okumura, Yasuo; Hirayama, Atsushi; et al.
Abstract: Background: Data on the effectiveness and safety of rivaroxaban for the treatment of patients with venous thromboembolism (VTE) and active cancer are limited in the Japanese real-world setting. Methods: In this subanalysis of the J'xactly study, which was a multicenter, prospective, observational study, we evaluated the effectiveness and safety of rivaroxaban in patients with acute VTE and active cancer (n = 193) versus those without active cancer (n = 823). Results: Compared with patients without active cancer, those with active cancer demonstrated a significantly different age distribution, with fewer aged <65 and ≥75 years; a lower proportion of women; a lower mean body mass index; and a lower proportion of physical inactivity, injury, thrombophilia, and heart failure. There was no difference in the initial dose distribution of rivaroxaban between patients with and without active cancer. The incidences of recurrence or aggravation of symptomatic VTE and major bleeding were not significantly different [VTE: 1.44 % vs. 2.80 % per patient-year, hazard ratio (HR) 0.50, 95 % confidence interval (CI) 0.18–1.39, p = 0.172; major bleeding: 4.49 % vs. 2.55 % per patient-year, HR 1.80, 95 % CI 0.82–3.95, p = 0.137]. Approximately 10 % of patients with active cancer died at 6 months, with a significantly higher cumulative all-cause mortality rate than those without active cancer (23.29 % vs. 2.03 % per patient-year, HR 11.31, 95 % CI 7.30–17.53, p < 0.001). Conclusions: In patients with VTE and active cancer, rivaroxaban showed acceptable effectiveness, although clinically significant bleeding remains a concern. Clinical trial registration: UMIN Clinical Trials Registry number, UMIN000025072. Graphical abstract: Unlabelled Image Highlights: Direct oral anticoagulants have demonstrated safety and effectiveness for venous thromboembolism (VTE) with active cancer. Data on rivaroxaban therapy for VTE are scarce in the Japanese real-world setting. The J'xactly study was a multicenter, prospective, observational study in Japan. Rivaroxaban showed acceptable effectiveness in patients with VTE and active cancer in Japan. Clinically significant bleeding remains a concern with rivaroxaban treatment.